Inflammatory Disorders and Atherosclerosis: New Therapeutic Approaches - Charakida, Marietta; O'Neil, Frank; Masi, Stefano; Papageorgiou, Nikolaos; Tousoulis, Dimitris (Current Pharmaceutical Design, 2011)
Recent evidence suggests that patients with chronic inflammatory disorders are at increased cardiovascular risk. A number of different mechanisms have been postulated to contribute to atherosclerotic disease progression in these patients including traditional cardiovascular risk factors, cytokine upregulation, immume mediated pathways and increased oxidative stress. Novel treatments target inflammatory pathways and have beneficial effect on rheumatic disease activity however; their impact on cardiovascular risk reduction remains unclear. Further longitudinal studies are required to assess the value of different therapeutic approaches on cardiovascular outcome of these patients.
Keywords: Inflammatory disorders